2001
DOI: 10.1074/jbc.m101062200
|View full text |Cite
|
Sign up to set email alerts
|

Predominant Identification of RNA-binding Proteins in Fas-induced Apoptosis by Proteome Analysis

Abstract: Proteome analysis of Jurkat T cells was performed in order to identify proteins that are modified during apoptosis. Subtractive analysis of two-dimensional gel patterns of apoptotic and nonapoptotic cells revealed differences in 45 protein spots. 37 protein spots of 21 different proteins were identified by peptide mass fingerprinting using matrix-assisted laser desorption/ionization mass spectrometry. The hnRNPs A0, A2/B1, A3, K, and R; the splicing factors p54 nrb , SRp30c, ASF-2, and KH-type splicing regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
95
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 58 publications
(52 reference statements)
7
95
0
Order By: Relevance
“…Earlier, we successfully identified novel caspase-3 and caspase-7 substrates using the degradomic approach (Lee et al, 2004;Jang et al, 2007). Thiede et al additionally reported that several proteins, including FBP-1, are modified in Jurkat T cells during apoptosis (Thiede et al, 2001). Data from this study show that FBP-1 is cleaved by caspase-3 and -7, both in vitro and during apoptosis induced by various stimuli.…”
Section: Introductionmentioning
confidence: 53%
“…Earlier, we successfully identified novel caspase-3 and caspase-7 substrates using the degradomic approach (Lee et al, 2004;Jang et al, 2007). Thiede et al additionally reported that several proteins, including FBP-1, are modified in Jurkat T cells during apoptosis (Thiede et al, 2001). Data from this study show that FBP-1 is cleaved by caspase-3 and -7, both in vitro and during apoptosis induced by various stimuli.…”
Section: Introductionmentioning
confidence: 53%
“…However, correlation between the results of different studies is usually low. This deviation might be due to differences in cell line, apoptotic inducer, proteomic techniques and experimental design (Thiede et al 2001;Thiede and Rudel 2004). For instance, the heterogeneous nature of non-induced CHO cultures likely influenced our DIGE results, as the populations assayed were composed of cells at different stages.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that αNAC may perform certain function in the absence of βNAC (Thiede et al, 2001;Spreter et al, 2005). To study the structure of human αNAC alone, we constructed a number of αNAC variants of different lengths, including the full length and the NAC domain alone (i.e., residues 80-133, named as TαNAC standing for truncated αNAC).…”
Section: Structure Of αNac Nac Domain Homodimermentioning
confidence: 99%
“…In the absence of a hetero-partner, for example when overexpression or downregulation of a single subunit, the remaining dominant subunit may have functions independent of nascent peptide binding (Thiede et al, 2001;Spreter et al, 2005). For instance, isolated αNAC is a multiple functional protein taking part in transcription regulation St-Arnaud, 1998;St-Arnaud and Quelo, 1998;Yotov et al, 1998), cell proliferation, and differentiation (Al-Shanti et al, 2004;Lopez et al, 2005;Al-Shanti and Aldahoodi, 2006).…”
Section: Introductionmentioning
confidence: 99%